Sequential trials in the context of competing risks: Concepts and case study, with R and SAS code. (17th May 2019) - Baayen, C.; Volteau, C.; Flamant, C.; Blanche, P.
Abstract : Sequential designs and competing risks methodology are both well established. Their combined use has recently received some attention from a theoretical perspective, but their joint application in practice has been discussed less. The aim of this paper is to provide the applied statistician with a basic understanding of both sequential design theory and competing risks methodology and how to combine them in practice. Relevant references to more detailed theoretical discussions are provided, and all discussions are illustrated using a real case study. Extensive R and SAS code is provided in the online Supplementary Material.